The Effect of Anagram Game Towards Students’ Vocabulary Mastery at the Eighth Grade of SMPN 6 Malingping Lebak Banten in the Academic Year 2023/ 2024 - Lida Asiatu Saripatu Dini; Ade Sudirman; Riandi (Innovations in Multidisciplinary Education Journal, 2024)
This research aims to determine the significant Effect of Anagram Game Towards Students Vocabulary Mastery at the Eighth Grade of SMPN 6 Malingping Lebak-Banten in the Academic Year 2023/2024. The researcher paper used quantitative approach and quasi-experimental design. This research was conducted six meetings and the researcher has chosen two classes are a experimental class and control class. The technique in choosing the sample is purposive sampling, the researcher used VIII-A (30 students) as experimental class and VIII-B (32 students) as control class. The experimental class was taught used Anagram Game, while the control class was taught used Pictionary Game. In the collecting the data technique, the researcher gives pre-test and post-test. The score pre-test of experimental class are 1965, the score pre-test of control class are 1730. Then, the score post-test of experimental class are 2340, the score post-test of control class are 2335. In analyzing the data, the researcher used SPSS 29 statistical computation and used the result of the post-test both class experimental and control to analyze the hypothesis test. The researcher has found the result of Significant two-tailed = <0.001. Therefore, the researcher concluded that the usage of Anagram Game has a significant effect towards students’ vocabulary mastery in SMPN 6 Malingping.